The Progressive Wave Approach Analyzing the Evolution of Shock Waves in Dusty Gas - Nath T.; Gupta R.K.; Singh L.P. (My University, 2025)
In the present paper the theory of progressive waves is used to analyze the finite amplitude disturbances, moderately small amplitude disturbances in a dusty gas for generalized geometry. The conditions, under which a complete history of the evolutionary behavior of shock waves including weak shock can be traced out, are determined. It is also assessed as to how the presence of dust particles in the gas affects the existence of shock or no shock. Further the effect of variation of mass fraction of the dust particles on the growth and decay behavior of shock in cylindrically symmetric and spherically symmetric flows are discussed. © 2017, Springer (India) Private Ltd.